ANALISIS PROFESIONAL KERJA KARYAWAN SEBAGAI IMPLEMENTASI ETIKA BISNIS DALAM PERUSAHAAN MULTI LEVEL MARKETING (MLM) (STUDI KASUS INDEPENDENT DISTRIBUTOR HERBALIFE CABANG REMBANG) - Angreani, Vannya Laksmi; Rodhiyah, Rodhiyah; Budiatmo, Agung (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2015)
Professional attitude is very important in carrying out its work. Professional work is the manner in which someone is able to apply the capability or expertise to be able to provide the best performance on the job. Sometimes the formation of a professional attitude of employees because of the company's business ethics are useful to provide guidance in running the business. No exception will Multi Level Marketing business that makes employees become a major asset in running the business. But in reality MLM Herbalife Apex branch employees' professional attitude in running business ethics is still low and often a lot of violations. Violations often occur on recruitment and sales for the product. The purpose of this study to determine the ethics of recruiting new downline, determine product pricing and granting discounts, as well as efforts to achieve professional work as the implementation of business ethics conducted by Herbalife distributor Rembang branch.Type of this research is exploratory. Retrieval technique is purposive sampling resources; data collection techniques done by in-depth interviews, observation, and documentation; data analysis techniques using test data by triangulation credibility, transferability test, and test konfirmability.Results and discussion in the Herbalife business are many violations as follows: recruiting a downline that does not comply with existing rules and product sales due to product price is too expensive, the achievement of distributors can see the performance of distributors who work full time and side. The conclusions are many distributors who are committed and professional work ethics so low that in the implementation of an already established business, there are several violations that resulted in delays in the process of doing business. His advice is more assertive and precise in addressing the violations that occurred and needs to be improved meeting capable of inflicting a professional attitude to work and inform about business ethics prearranged.